إضاءات على التفسير الكمي لمنحنيات السبر الكهربائي الشاقولي" (Latakia University Journal -Basic Sciences Series, 2014)
يتوصل البحث إلى إمكانية تفسير منحنيات السبر الكهربائي الشاقولي لمنحنيات حقلية حقيقية, بعد أن تم التوصل إلى حساب المقاومية الظاهرية من خلال معادلة صالحة لجميع التشكيلات. V(r)=I/2 πr[C1pn+T() + C2p1] نتائج البحث توفر الكثير من الوقت والجهد في معالجة و تفسير المعطيات الجيوكهربائية, وتنعكس ايجابيا على تفسير السبر الكهربائي الشاقولي أكاديمياً و تطبيقياً. Paper  Find the possibility of interpreting the vertical electrical sounding curves in real field , having been reached resistivity virtual account through the equation is valid for all configurations V(r)=I/2 πr[C1pn+T() + C2p1] Search results provide a lot of time and effort in processing and interpretation of the geoelectrical data , and reflected positively on the interpretation of the vertical electrical sounding academic and an applied.